How much mixed/boundary friction is there in an engine — and where is it?. (October 2020) - Taylor, RI; Morgan, N; Mainwaring, R; Davenport, T
Automotive engines are believed to operate predominantly in the hydrodynamic regime, as evidenced by the (1) the successful strategy of reducing lubricant viscosity to reduce engine friction and improve vehicle fuel consumption, and (2) for most engine operating conditions, direct measurements of engine friction (either motored or fired) find that engine friction increases with increasing engine speed. However, certain components in an engine are known to operate mainly in the mixed/boundary lubrication (e.g. the valve train) and other components (such as the piston rings) operate in the mixed/boundary regime for a portion of the time. In order to quantify the amount of mixed/boundary lubrication in an engine, and in the individual components of the engine, motored and fired friction tests have been carried out for a range of lubricants (of differing viscosity grade, and with/without friction modifier additives). A full discussion of the implications of this work, which includes the impact of fuel dilution and "running-in" is included with insights given into how the work reported here guides the development of future fuel-efficient engine lubricants.